A06 Effects of mutant huntingtin on cortical neuron connectivity and activity dependent gene expression. (16th November 2010) - Seredenina, T; Gambazzi, L; Gokce, O; Katsyuba, E; Runne, H; Markram, H; Giugliano, M; Luthi-Carter, R
Abstract : Background: Huntington's disease (HD) is a genetic neurodegenerative disorder characterised by prominent motor and cognitive abnormalities. Although previous studies of HD have addressed many potential mechanisms of striatal neuron dysfunction and death, it is also known based on clinical findings that cortical function is dramatically disrupted in HD. Aims: We set out to establish a new cortical neuron model of HD and to use this model to define new molecular and neuronal circuit bases for the cortical effects of mutant huntingtin (htt). Methods: We studied the relation between the molecular effects of mutant htt fragments in cortical cells and the corresponding behaviour of cortical neuron microcircuits using primary rat cortical neurons transduced with lentiviral expression vectors expressing 171 aa N terminal fragments of wild-type (18Q) or mutant (82Q) htt. Results: We found that population burst firing was abnormal in neurons expressing mutant htt, and that this behaviour was normalised by exogenous administration of BDNF. We further demonstrated that a specific decrease in the activity dependent component of BDNF expression was impaired in 82Q htt exposed neurons prior to the change burst firing behaviour. Exon specific analysis of BDNF transcripts showed specific abnormalities in the induction of transcripts IV and VI in 82 htt expressing cells. Conclusions: These data elucidate a novel HD related deficit in BDNF gene regulation as a plausible mechanism of cortical neuron hypoconnectivity and cortical function deficits in HD. The mechanism(s) underlying the deficiency in activity dependent transcription of BDNF appear to be distinct from NRSF/REST which specifically regulates BDNF transcripts I, II and III.